Assessment of levels of some physico-chemical parameters and heavy metals of Orisa River, Omu-Aran, Nigeria - O. O. ELEMILE; O. P. FOLORUNSO; O. O. IBITOYE (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
The loss of water quality in rivers has been extremely serious in developing countries due to the concentrated human activities along the rivers; this could have negative impact on sustainable development. Little or no information about river water quality is available in Nigeria with no exception to Omu-Aran. Levels of the physicochemical and heavy metals parameters of River Orisa, Omu-Aran, Nigeria were assessed. Thirty water samples were collected from five different points along the River with three water samples taken twice a month between September 2018 and January 2019. The samples were analyzed for twelve physicochemical parameters in the Laboratory while the heavy metals were determined using atomic absorption spectroscopy. Standard methods were used to determine the physicochemical characteristics of the water. The analysis of data was performed using descriptive statistics and MANOVA at α_0.05. The mean values of parameters in the water samples from various points varied from 29.72 ± 1.66 to 74.06 ± 22.44 μs/cm, 0.13 ± 0.06 to 1.05 ± 0.86 mg/L and 0.43 ± 0.47 to 2.21 ± 2.19 mg/L for electrical conductivity, chromium and nickel, respectively. The values of the water quality parameters differed significantly except that of total hardness, calcium, magnesium, sulphate, lead, copper, nickel and iron. Findings reveal the tendency of bioaccumulation in the river as all the heavy metals except Zn were above the WHO Standards. There is therefore the need for constant observation of heavy metal parameters in the river course for the preservation of marine and human lives.